PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE TERHADAP KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2012 - Fitri Ella Fauziah (STIE Pelita Nusantara Semarang, 2015)
This study aimed to examine the effect of economic performance, environmental performance and social performance are the three focus disclosures in the Global Reporting Initiative on financial performance. As for sales as a proxy for financial performance. Samples were obtained by using purposive sampling. This study used secondary data obtained through the financial statements and annual reports of non-financial companies listed on the Stock Exchange. The study states that the economic performance and significant positive effect on financial performance, environmental performance and no significant negative impact on financial performance, while social performance and significant negative impact on financial performance. The test results simultaneously provide results that there is a significant effect for all the independent variables on the dependent variable.